2017
DOI: 10.2147/opth.s141313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age, sex, and refractive errors on central corneal thickness measured by Oculus Pentacam<sup>&reg;</sup>

Abstract: BackgroundCentral corneal thickness (CCT) can be used to assess the corneal physiological condition as well as the pathological changes associated with ocular diseases. It has an influence on the measurement of intraocular pressure and is being used as a screening tool for refractive surgery candidates. The aim of this study was to determine the median CCT among normal Pakistani population and to correlate CCT with age, sex, and refractive errors.MethodsWe conducted a retrospective analysis of 5,171 healthy ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…Similarly, according to Gelawet [29], they are in conflict with some earlier findings where the average was higher in males than in females, while according to Hahn, in the oldest CCT the least apparent [26]. According to the study of Hashman N, they showed that males had significantly smaller skin corneas than females [30]. Also CCT did not show any gender difference, according to M. Micheal [20].…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, according to Gelawet [29], they are in conflict with some earlier findings where the average was higher in males than in females, while according to Hahn, in the oldest CCT the least apparent [26]. According to the study of Hashman N, they showed that males had significantly smaller skin corneas than females [30]. Also CCT did not show any gender difference, according to M. Micheal [20].…”
Section: Discussionmentioning
confidence: 70%
“…Hashmani et al found that the astigmatic refractive error affected central corneal thickness. 12 The cylinder values were found to have a positive correlation with CCT, with a r-value of 0.154.…”
Section: Discussionmentioning
confidence: 90%
“…Sample sizes of subjects in first, sixth and seventh decade were so small and could not be evaluated. 12 On the other hand, Atchison et al found no significant correlation between central corneal thickness and age by using Scheimpflug topography. 13 In these studies, the age ranged between 10, 20 years and 70 years and refractive status was variable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also conceivable that the differences in CCT noted may have been due to genuine changes in CCT rather than measurement error. For example, numerous cross-sectional studies have suggested CCT decreases with age [16][17][18][19][20][21][22][23] . and changes in corneal hydration might affect measurements.…”
Section: Discussionmentioning
confidence: 99%